Poverty is growing in Puerto Rico, under US colonialism: 57.6% of children live in poor households - Norton, Ben (Geopolitical Economy Report, 2023)
Poverty is rising in one of the world’s oldest colonies: In Puerto Rico, 41.7% of people, including 57.6% of children, live in poverty. This is nearly four times the US rate.